Lily Quench and the hand of Manuelo - Prior, Natalie Jane 1963- (Puffin Books, 2004)
When Lily, Queen Dragon, and King Lionel follow Murdo in his flight to the Black Mountains, they become involved with a revolution led by the mysterious Manuelo.